2014
DOI: 10.1371/journal.pone.0111960
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite Nanoparticles Inhibit Tumor Growth and Upregulate the Expression of P53/P16 in Ehrlich Solid Carcinoma Bearing Mice

Abstract: BackgroundMagnetite nanoparticles (MNPs) have been widely used as contrast agents and have promising approaches in cancer treatment. In the present study we used Ehrlich solid carcinoma (ESC) bearing mice as a model to investigate MNPs antitumor activity, their effect on expression of p53 and p16 genes as an indicator for apoptotic induction in tumor tissues.MethodMNPs coated with ascorbic acid (size: 25.0±5.0 nm) were synthesized by co-precipitation method and characterized. Ehrlich mice model were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
(41 reference statements)
2
15
1
Order By: Relevance
“…The results of the study have demonstrated that treatment by vitamin A and olive oil has no prevention or productive effect. These results are in agreement with [15]who reported that P16 and P53have important roles in the inhibition of cell proliferation via cell cycle arrest and apoptosis. They are mutated in many tumor cell types [16].Human telomerase reverse transcriptase TERT, which regulates telomere length and can promote tumor development, increases the anti-apoptotic capacity of cells and enhance repair.…”
Section: Discussion:-supporting
confidence: 93%
See 3 more Smart Citations
“…The results of the study have demonstrated that treatment by vitamin A and olive oil has no prevention or productive effect. These results are in agreement with [15]who reported that P16 and P53have important roles in the inhibition of cell proliferation via cell cycle arrest and apoptosis. They are mutated in many tumor cell types [16].Human telomerase reverse transcriptase TERT, which regulates telomere length and can promote tumor development, increases the anti-apoptotic capacity of cells and enhance repair.…”
Section: Discussion:-supporting
confidence: 93%
“…However, our results are in agreement with more recent studies, which showed that high levels of these supplement may increase cases of gastrointestinal cancers, such as stomach, colon, and esophageal, in some populations. [15] In the current study, although there were no significant decrease in the final CT between the olive oil and vitamin treated groups and tumor untreated group,P16and P53 expression levels were increased with olive oil and vitamin A treated groups (decreased TC) compared to tumor untreated group (maximum TC). The results of the study have demonstrated that treatment by vitamin A and olive oil has no prevention or productive effect.…”
Section: Discussion:-contrasting
confidence: 57%
See 2 more Smart Citations
“…As we all know, one of the main challenges in disease treatment is how to manipulate drugs toward a particular site. Although there have been some promising strategies, it is hard for drugs to reach to the lesion precisely . Fortunately, magnetic NPs (MNPs) enable the targeted delivery of drugs in vitro and in vivo …”
Section: Drug Deliverymentioning
confidence: 99%